Efficiency of Post-War Integration of Corporate Structures in Ukraine Based on the Strategic Connection Framework™ Methodology - Cherep, Nataliia (Актуальні питання економічних наук, 2025)
The relevance of this study is driven by the growing role of nonfinancial factors in mergers and acquisitions (Mergers and Acquisitions, hereafter M&A) in emerging markets under conditions of geopolitical instability. In contemporary transactions, alongside the financial parameters of an asset, increasing importance is attached to trust between counterparties, which influences the pace of negotiations, the stability of agreed terms, and the probability of deal completion. At the same time, in most M&A models trust remains a nonformalized variable that is not integrated into the operational architecture of transaction management. The aim of this article is to provide a theoretical justification and empirical verification of a model for managing trust as a measurable operational asset in M&A processes in emerging markets under conditions of geopolitical instability, based on the Strategic Connection Framework™ (hereafter SCF). The research methods are based on systemic and structural functional analysis of the evolution of approaches to the interpretation of trust in M&A, the adaptation of the SCF to the transaction cycle, and a comparative case analysis of documented transactions in the Ukrainian market. The study also applies a method of operationalizing qualitative indicators through a semi quantitative scale for evaluating trust indicators. The results of the study demonstrate that trust can be interpreted as an operational asset integrated into the structural, procedural, and reputational components of a transaction. It is established that the stability of the communication architecture of a deal correlates with a reduction in the negotiation cycle, the preservation of agreed financial parameters, and a decrease in the perceived risk premium. The findings confirm the feasibility of integrating trust indicators into due diligence procedures and of forming a “trust profile” of a company before entering the market. The conclusions substantiate that trust management should be systematically integrated into the preparation of M&A transactions as a controllable factor in achieving the planned transactional outcome. The SCF model can be used as an applied instrument for designing the communication architecture of a transaction aimed at increasing its coherence and effectiveness. Prospects for further research are associated with the development of standardized metrics for measuring trust and with the quantitative assessment of its impact on financial parameters and the long term effectiveness of corporate integration.